Health-related quality of life in the ENDEAVOR study: carfilzomib-dexamethasone vs bortezomib-dexamethasone in relapsed/refractory multiple myeloma - Ludwig, Heinz; Moreau, Philippe; Dimopoulos, Meletios A; Mateos, Maria-Victoria; Kaiser, Martin; Hajek, Roman; Feng, Shibao; Cocks, Kim; Buchanan, Jaqueline; Weisel, Katja (Blood cancer journal, 2019)
We examined effects of carfilzomib-dexamethasone (Kd56) versus bortezomib-dexamethasone (Vd) on health-related quality of life (HR-QoL) in relapsed/refractory multiple myeloma (MM) patients from the ENDEAVOR study. HR-QoL was assessed by the European Organisation for Research and Treatment of Cancer QoL Questionnaire (QLQ-C30), MM-specific module (QLQ-MY20), and Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity (FACT-GOG-Ntx) "Additional Concerns" neurotoxicity subscale. The QLQ-C30 Global Health Status (GHS)/QoL scale and seven prespecified subscales were compared between groups using mixed model for repeated measures. Of 929 randomized patients, 911 with ≥1 post-baseline assessment were included. Kd56 was associated with statistically significant improvements in GHS/QoL, fatigue, pain, side effects, and FACT/GOG-Ntx scores versus Vd, although mean differences did not meet thresholds for clinical significance. The Kd56 group had longer time to deterioration (TTD) in GHS/QoL (median 3.7 versus 2.8 months, p = 0.0046), physical function (5.6 versus 3.7 months, p = 0.0390), nausea/vomiting (17.6 versus 8.2 months, p = 0.0358), side effects (6.4 versus 3.7 months p < 0.0001), and FACT/GOG-Ntx (11.1 versus 5.5 months, p = 0.0004). Overall, Kd56 resulted in statistically but not clinically significant improvements in mean GHS/QoL scores versus Vd. Treatment with Kd56 versus Vd also significantly prolonged TTD in GHS/QoL, physical function, nausea/vomiting, side effects, and FACT/GOG-Ntx.
Keywords: senioři; Oligopeptides; senioři nad 80 let; Multiple Myeloma; výsledek terapie; adherence pacienta; Bortezomib; průzkumy a dotazníky; Middle Aged; mužské pohlaví; oligopeptidy; Neoplasm Recurrence, Local; lokální recidiva nádoru; kvalita života; Health Care Surveys; chemorezistence; Aged, 80 and over; Neoplasm Staging; mnohočetný myelom; ženské pohlaví; bortezomib; Humans; Drug Resistance, Neoplasm; dexamethason; Surveys and Questionnaires; průzkumy zdravotní péče; Patient Compliance; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; staging nádorů; protokoly protinádorové kombinované chemoterapie; Dexamethasone; Female; Aged; Quality of Life; Treatment Outcome; lidé; Male